The Role of Gender in Language and Communication: A Linguistic Perspective - Irma Nuraeni Salsabila; Aldo Faisal Umam; Aisyah Nurjanah; Olyvia Wahyuningsih; Anisa Ayu Dwi Lestari (Eduvest - Journal of Universal Studies, 2024)
Language is an important communication tool in everyday life, and an understanding of how language reflects and shapes gender roles can provide valuable insights into the social construction and perception of gender in society. The purpose of this study is to explain gender roles in language and communication from a linguistic perspective. This research uses a qualitative approach. Data collection techniques in this study were carried out by exploring books, journals and other information relevant to the research. Data analysis in this study involves identifying gender-related language patterns and structures, using linguistic theoretical frameworks such as sentence structure analysis, pragmatic analysis, sociolinguistic analysis, and so on. The results show that in everyday language use, there are clear patterns in the use of words, phrases, and language constructions that perpetuate gender stereotypes. This reflects the way people perceive and understand gender roles in social contexts. In addition, research also shows differences in communication patterns between men and women, including speaking styles, body language use and communication preferences. These differences reflect social and cultural influences that affect how individuals express themselves and interact.